Changes in the Configuration of the Fresh Water Lens due to ASRRG, Western Part of the Tiny Pari Island, Seribu Islands, Jakarta, Indonesia - Edi Prasetyo Utomo; Ananta Purwoaminta; Yayat Sudrajat (Pusat Survei Geologi, 2017)
Pari Island (Pulau Pari) is a small coral island in the Seribu Islands group off the north coast of the Jakarta Capital Special Region. Government has planned to develop this island into a tourist attraction because of its beautiful environment. However, the government development plans have not included facilities to meet the demand for groundwater, which represents the principal resource to meet the demand for freshwater. Pari Island has limited resources of groundwater due to the small size of the area where recharge of groundwater from rainfall can take place. A problem will arise that with the increase of visitors to the island the demand for freshwater will increase, whileÂ groundwater resources of the island are very limited and dominated by brackish and saline groundwater. The objective of this research was to explore the possibility to increase the resources of fresh groundwater of Pari Island to support the increasing demand of fresh water. The method employed in the research is the application of ASRRG technology by the injection of the largest possible volume of rainwater and monitor changes of electrical conductivity and geoelectrical resistivity. Installation of an ASRRG network proved effective in lowering the salinity of groundwater in small islands. By increasing pore volume from 30% to 60% salinity decreases by 77%, which is reflected by the effect that the fresh groundwater lens which before comprised brackish water became fresh water with a thickness of 2.5 meter. The gain in pore volume equaled the decrease in salinity.Key words: Artificial recharge, Island hydrology, Salt-water/fresh-water relations, Indonesia